2011
DOI: 10.11606/issn.2238-6149.v22i2p162-171
|View full text |Cite
|
Sign up to set email alerts
|

Tempo de engajamento nas áreas de ocupação de adolescentes inseridos em uma escola publica

Abstract: Federal do Triângulo Mineiro (UFTM)-aprovado pelo Comitê de Ética da UFTM de acordo com o parecer nº 1555. 1. Graduada pelo do Curso de Terapia Ocupacional da Universidade Federal do Triângulo Mineiro-UFTM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
8

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 4 publications
2
2
0
8
Order By: Relevance
“…Studies such as the ones conducted by Carvalho and Machado 13 , Sarriera et al 20 and Martins and Gontijo 18 , as well as our study, which was developed after the studies of Barros et al in 2002, reaffirm such necessities and also indicated the need for more investment in leisure, sports and additional education for the young population of lowincome classes.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Studies such as the ones conducted by Carvalho and Machado 13 , Sarriera et al 20 and Martins and Gontijo 18 , as well as our study, which was developed after the studies of Barros et al in 2002, reaffirm such necessities and also indicated the need for more investment in leisure, sports and additional education for the young population of lowincome classes.…”
Section: Resultssupporting
confidence: 83%
“…Although researches with Brazilian children with the categorization of activities and times similar to those here presented could not be found, some similar results appear in national researches about the time use of children and adolescents 1,2,13,[18][19][20]22 . The study by Martins and Gontijo 18 was the one that presented activity categories closer to the ones presented in this study; however, the age of the participants ranged between 12 and 16 years.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Estes resultados são compatíveis com os resultados de pesquisas que avaliaram a qualidade de vida da população infanto-juvenil em idade escolar: Uma síntese dos resultados obtidos em estudos sobre o uso do tempo com crianças e adolescentes de classe popular aponta para a necessidade de maior envolvimento da instituição escolar como entidade promotora do consumo de bens culturais e na promoção da conscientização da necessidade do cultivo de hábitos e estilos de vida mais saudáveis, por meio de práticas regulares de atividades físicas e de atividades de lazer mais ativas, já que a taxa de participação em atividades de lazer passivo como assistir TV e usar o computador e a baixa taxa de participação em atividades extracurriculares e culturais são constantemente encontrados nestes estudos (BARROS et al, 2002;CARVALHO;MACHADO 2006;SARRIERA et al, 2007;MARTINS;GONTIJO, 2011;SCHWERTNER;FISCHER, 2012;SOUSA;EMMEL, 2013;NUNES et al, 2013 …”
Section: Correlações: Tempo Satisfação Significado E Qualidade De Vunclassified